To be or not to be the queerest of them all: Investigating the Freedom of Gender Performativity within the Queer Space of Cosplay/Cross play - Loke, Elween (2016)
This paper examines freedom of gender performativity among Crossplayers and Cosplayers within the queer space in which they embody gendered identities. Cosplay refers to acts of role-playing based on characters from anime and manga, or Japanese animation and comic respectively. Crossplay, on the other hand, is similar to Cosplay, except that participants dressed up as characters that are of their opposite gender. While Cosplay is already regarded as a queer activity, Crossplay is observed as the queerest among the queer, as it defies the traditional gender norms in patriarchal country like Malaysia. This research is significant as both Malaysian Cosplay subculture (and Crossplay), which is increasingly popular, remained understudied, as well as issues with regard to the deviant aspect of gender performativity. Using data collected from in-depth interviews with eight respondents and four sessions of participant observation at various Cosplay events, the researcher observed interactions between Crossplayers and Cosplayers, and subsequently analysed the findings to provide insights into freedom of gender performativity within the queer space. Findings and analyses showed that, while the queer space provides a space for participants to construct their very own gender identity, it is not independent of the influence of the traditional gender dichotomy. As far as the discourse of gender is concerned, the queer space inevitably becomes hierarchical. While the queer space tends to create the illusion for non-participants to acknowledge the exercise of gender freedom, it by no means guarantees freedom of gender performativity